(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To evaluate test-retest reliability of physical fitness measures in hip osteoarthritis (OA) patients and assess longitudinal changes in these parameters following total hip arthroplasty (THA). This study incorporates previously unexamined parameters like V̇O2peak and trunk endurance, alongside physical activity monitoring through accelerometry and self-reported outcomes in 1-year follow-up. Methods: Seventy-eight patients (mean age 74 ± 4.5 years, 81% women) scheduled for THA performed physical fitness tests and accelerometry-measured physical activity. The test battery included muscle strength, motor fitness, and cardiorespiratory fitness. Assessments were conducted at two pre-operative timepoints and at 4-month and 1-year post-operative follow-up. Physical activity was objectively measured using hip-worn triaxial accelerometers. Results were compared with healthy older adults. Statistical analyses included test-retest reliability assessment, between-group comparisons, and longitudinal change analysis using repeated measures ANOVA. Results: Good to excellent test-retest reliability was demonstrated for most fitness parameters. Pre-operatively, hip OA patients showed significant deficits compared to healthy controls in moderate-to-vigorous physical activity (18.7 vs 44.7 min/day) and multiple physical fitness parameters. At 1-year post-op, significant improvements were observed in 23 of 45 measured parameters, including functional mobility (Timed Up and Go: –29%), walking distance (Six-Minute Walk Test: +16%), trunk endurance-strength (+71–82%), shoulder-press (+33%), various leg strength tests (+13–42%), and 4 m max walking-speed (+42%). Moderate-to-vigorous physical activity increased by 63% and daily step count improved from 6,004 to 7,558 steps/day (+26%). Notably, ipsilateral-to-contralateral step height asymmetry decreased from 27% pre-operatively to 8% at 1-year. V̇O2peak demonstrated modest but significant improvement from 22.7 to 23.6 mL/kg/min 1-year postoperatively (+4%). Conclusion: This study highlights significant pre-operative functional deficits in patients with hip osteoarthritis, with substantial improvements observed across multiple performance domains 1-year post-surgery. Notably, patients failed to meet the recommended physical activity guidelines prior to surgery but achieved them post-operatively. The demonstrated reliability of the test battery reinforces its value for both research and clinical applications.